FOXL2 Mutation is Absent in Uterine Tumors Resembling Ovarian Sex Cord Tumors. (May 2015) - Chiang, Sarah; Staats, Paul N.; Senz, Janine; Kommoss, Friedrich; De Nictolis, Michele; Huntsman, David G.; Gilks, C. Blake; Oliva, Esther
<x xml:space="preserve">Abstract</x> Uterine tumors resembling ovarian sex cord tumors (UTROSCTs) are rare uterine neoplasms characterized by pure or predominant epithelial-like patterns that share morphologic, immunohistochemical, and ultrastructural features with ovarian sex cord tumors. FOXL2 immunoexpression has recently been found in sex cord stromal tumors of the ovary, including granulosa cell tumors, Sertoli-Leydig cell tumors, thecomas, and fibromas, but mutations have been identified mostly in adult granulosa cell tumors. In this study, we investigated FOXL2 mutation status and protein expression in UTROSCTs. Mutational analysis using a TaqMan real-time polymerase chain reaction–based allelic discrimination assay was performed on formalin-fixed, paraffin-embedded tissue from 15 UTROSCTs. FOXL2 mutation was absent in all tumors. FOXL2 immunoexpression was tested in all 15 tumors. Intensity of staining was scored as weak, moderate, or strong. Percentage of tumor cells with nuclear staining was recorded as follows: 0 (negative); 1+ (1% to 25%); 2+ (26% to 50%); 3+ (51% to 75%); and 4+ (76% to 100%). Nuclear expression of FOXL2 was present in 6 of 15 (40%) UTROSCTs. One tumor demonstrated strong 4+ staining. Moderate expression was seen in 3 cases, including 2 and 1 showing 2+ and 1+ staining, respectively. Weak expression was observed in 2 tumors demonstrating 3+ and 1+ staining. Although UTROSCTs show overlapping morphologic, immunohistochemical, and ultrastructural features with sex cord stromal tumors of the ovary, they do not harbor FOXL2 mutation despite focal immunoreactivity in a subset of these tumors.